Perioperative parenteral nutrition. - Muguruza, Alvaro; Bertullo, Hugo; Duarte, Gladys; Fontora, Gloria; Ferradas, Ana (Cirugía del Uruguay, 1984)
Forty surgical patients with digestiva illness, were nutrltlonally supported by parenteral route in the pre and post operatory.